SISTEM PENGELOLAAN USAHA PETERNAKAN KERBAU MOA DI PULAU MOA, KABUPATEN MALUKU BARAT DAYA - Aprilin Lensya Mandaka; Jomima Martha Tatipikalawan; Abraham Henry Tulalessy (PT. BARRINGTONIA ASIATICA LESTARI, 2025)
This study aims to examine the characteristics of farmers and the management system of Moa Buffalo farming in Moa Island, Southwest Maluku Regency. A descriptive qualitative and quantitative method was applied, with data collected through interviews, field observations, and focus group discussions in three villages: Tounwawan, Werwaru, and Patty. Results showed that most farmers are of productive age, have basic education, and 5–20 years of experience. The majority manage buffalo as a side activity, own the livestock, and rely on family labor. The dominance of adult female breeders indicates high reproductive potential and opportunities for local breeding development. Moa Buffalo serves multiple economic and socio-cultural functions, such as income source, savings, and social status symbol. The farming system combines semi-intensive and extensive practices depending on the season. Communal housing is used via the “lutur” system. Feed is mainly grass and tree legumes without concentrated use. Reproduction occurs naturally without control, raising the risk of inbreeding. Traditional medicine is commonly used for animal health, and marketing relies on village and inter-island traders.